Study protocol: Feasibility of medically tailored meals for pediatric populations at risk for disparities in serious illness outcomes due to inequities in food-related social drivers of health (MTM-Kids). - Bridgette Thom; Victoria R Crowder; Andrew B Smitherman; Bethany S Cosgrove; Rebecca Bosch; Yashvi Vardhan; C Natasha Matt; Alice Ammerman; Sheila Judge Santacroce (PLoS ONE)
Background Food and nutrition insecurity are actionable, clinically relevant social determinants of health that disproportionately affect pediatric populations, particularly those with serious illnesses, including cancer. Lack of consistent access to nutritious food contributes to poorer treatment tolerance, increased infection risk, lower quality of life, and worsened long-term health outcomes. Medically-tailored meals (MTM) have shown promise in improving health outcomes in adults with diet-sensitive conditions, but their feasibility and acceptability in pediatric populations remain unexplored. The Medically Tailored Meals for Pediatric Populations at Risk for Disparities in Serious Illness Outcomes due to Inequities in Food-Related Social Drivers of Health (MTM-Kids) study aims to assess feasibility of providing medically tailored meals to adolescents undergoing cancer treatment, with a focus on recruitment, retention, parental cost-coping, and preliminary impact on food-related insecurities,. Materials and methods This study will enroll 15 adolescent-parent dyads from a pediatric oncology clinic. Participants will receive weekly deliveries of up to 10 frozen medically tailored meals over a 12-week intervention period. Feasibility will be assessed based on recruitment, retention, and adherence to study requirements. Acceptability and appropriateness of the intervention will be evaluated using surveys and semi-structured interviews conducted at 4, 8, and 12 weeks. Secondary outcomes include changes in household food insecurity, financial burden, and parental time demands as well as reported meal satisfaction and chemotherapy-related taste alterations. Quantitative data will be analyzed descriptively, and qualitative data will undergo thematic analysis. Discussion The study will provide critical insights into the feasibility of implementing medically tailored meals for pediatric oncology and other patients. Findings will inform the design of a future randomized controlled trial assessing the efficacy of MTM in improving nutritional status, treatment outcomes, and overall well-being in this vulnerable population. MTM-Kids may serve as a scalable intervention to address health disparities related to food insecurity in pediatric populations with serious illness. Trial registration ClinicalTrials.gov NCT06814795.